2018
DOI: 10.1016/j.chempr.2018.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Cathodically Stable Li-O2 Battery Operations Using Water-in-Salt Electrolyte

Abstract: Development of the Li-O 2 battery as a practical energy storage technology has been underpinned by the lack of a stable electrolyte to enable reversible conversion between O 2 and Li 2 O 2 , given that previous applied organic electrolytes all show reactivity toward reactive oxygen species. Wang and colleagues show that this issue can be solved with a water-in-salt electrolyte that contains no organic solvent molecules. The net result is a highly effective electrolyte that enables stable Li-O 2 battery operati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 73 publications
2
62
0
2
Order By: Relevance
“…Even in nonaqueous electrolytes, some reports stressed the essential role of a small amount of water in the electrolyte for achieving a high capacity (associated with the formation of toroidal www.advenergymat.de www.advancedsciencenews.com structure). [186] In the superconcentrated solution of LiTFS, the Li-O 2 battery was stable during 300 cycles. [183] Nonetheless, an excess amount of water molecules in the electrolytes results in the formation of LiOH, which might have a parasitic effect.…”
Section: Li-o 2 Batteriesmentioning
confidence: 99%
See 2 more Smart Citations
“…Even in nonaqueous electrolytes, some reports stressed the essential role of a small amount of water in the electrolyte for achieving a high capacity (associated with the formation of toroidal www.advenergymat.de www.advancedsciencenews.com structure). [186] In the superconcentrated solution of LiTFS, the Li-O 2 battery was stable during 300 cycles. [183] Nonetheless, an excess amount of water molecules in the electrolytes results in the formation of LiOH, which might have a parasitic effect.…”
Section: Li-o 2 Batteriesmentioning
confidence: 99%
“…[184,185] Dong et al used a water-in-salt electrolyte and showed the characteristic toroidal structure could be formed as well as the conventional organic electrolyte. [186] In the superconcentrated solution of LiTFS, the Li-O 2 battery was stable during 300 cycles. Figure 7 compares the mechanisms and the electrochemical performance of the same Li-O 2 battery in the waterin-salt electrolyte with the conventional organic electrolytes namely 0.1 m LiTFSI in N,N-dimethylacetamide (DMA) and dimethyl ether (DME).…”
Section: Li-o 2 Batteriesmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Nonetheless, inspired by organic superconcentrated electrolytes, 8,9 Suo et al recently proposed a new class of "aqueous" electrolytes, described as Water-in-Salt Electrolytes (WiSEs), obtained by dissolving large quantities of lithium bis(trifluoromethanesulfonyl)amide (LiTFSI) salt in water (more than 20 moles per kilogram of water) and in which a fluorinated based SEI was reported to be formed on the surface of electrodes. 10 Thus, these so-called WiSEs have recently been investigated in depth for the realization of practical LiBs [11][12][13][14][15] , but also for other applications such as sodium-ion, 16 potassium-ion, 17 lithium-air 18 batteries or even supercapacitors. 19 It is well established that the formation of the SEI on the surface of the negative electrode that prevents water reduction during the cell operation involves TFSI degradation.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure b, due to the initial activation process, the overpotential in the first cycle was ≈1.24 V; however, it reduced to ≈1.11 V at the 10th cycle and slowly increased to ≈1.19 V after 50 cycles. The slight increase in overpotential can be ascribed to the decomposition of the electrolyte during the repeated charge/discharge processes . Figure c further demonstrates the terminal potentials at each discharge and charge step over 50 cycles.…”
Section: Resultsmentioning
confidence: 92%